Engineering tribology - Stachowiak, G. W. (Gwidon W.); Batchelor, A. W. (Andrew W.) (Butterworth-Heinemann, 2014)
Provides a thorough understanding of friction and wear using technologies such as lubrication and special materials. This book focuses in particular on hydrodynamic, elastohydrodynamic, and hydrostatic lubrication techniques and examines all manner of wear, including abrasive, adhesive, corrosive, and fatigue